Five Paintings in the Oval Cartouches - Temples of India Project Team (Jio Institute, 2024)
Seen here are five paintings in the oval cartouches, in the ceiling of the mandapa (pillared hall) of the Bhandasar Temple. The oval shapes of the paintings are designed like mirror frames. This style is influenced by European paintings, especially the Company style paintings produced during the 18th – 19th centuries CE. The lower row depicts stories of Jinadatta Suri’s miracles when he made a dead cow, which was in front of the Jain temple, alive and put it in front of a Hindu temple. The left oval has a painting of Jinadatta Suri miraculously saving the Mughal prince. In the upper row are paintings of (left to right of the viewer) the sacred Meru mountain, Bahubali and Rishabnatha.